2001
DOI: 10.2118/01-07-02
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Group Analysis of Petroleum Fractions in Unconsolidated Porous Media

Abstract: A fast and accurate method for the group analysis of crude oils in porous media that describes petroleum components (especially heavy fractions) has been developed. NMR structure group analysis is used as the tool for the characterization of crude oils. This method is proposed as an alternative to existing complicated and laborious methods of characterization of extracted oil samples. Currently, group analysis of heavy fractions of crude oils is being investigated by means of chromatographic methods, such as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…However, the ranges are not constant and vary with oil viscosity and the amount and type of solvent used. It was shown that NMR analysis of heavy oil, both in bulk and in-situ, provided similar results for the percentages of saturates, asphaltenes, resins and aromatics in conventional SARA analyses [87]. However, the NMR method has the potential advantage over conventional techniques that it can be used in-situ and may have possible applications in downhole characterization.…”
Section: Solvent Effects and Heavy Oil Component Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…However, the ranges are not constant and vary with oil viscosity and the amount and type of solvent used. It was shown that NMR analysis of heavy oil, both in bulk and in-situ, provided similar results for the percentages of saturates, asphaltenes, resins and aromatics in conventional SARA analyses [87]. However, the NMR method has the potential advantage over conventional techniques that it can be used in-situ and may have possible applications in downhole characterization.…”
Section: Solvent Effects and Heavy Oil Component Analysismentioning
confidence: 98%
“…In one study, an attempt was made to use NMR relaxation measurements to analyse petroleum fractions in unconsolidated porous media [87]. NMR can be used to determine oil components, as the mobility of the nuclei is different in the different hydrocarbons present.…”
Section: Solvent Effects and Heavy Oil Component Analysismentioning
confidence: 99%
“…NMR measurements are simple and non-destructive, but capable of yielding an incredible wealth of information about the reservoir fluid under investigation in a particular sample (9) (10) . The mixture viscosity decreases dramatically as the ratio of the injected solvent to heavy oil or bitumen increases, and different solvents show different dilution capacity.…”
Section: Canadian Institute Of Mining Metallurgy and Petroleummentioning
confidence: 99%
“…NMR spectroscopic technique has long been used for both qualitative (Gillet et al 1980;Kvalheim et al 1985) and quantitative (Srivastava 1982;Allen 1985;Abu-Dagga and Ruegger 1988;Smirnov et al 1992;Sarpal et al 1998;Bansal et al 2007;Bansal et al 2014;Mirotchnik et al 2001;Young and Galya 1984;Poveda and Molina 2012) studies of petroleum products. The main focus of these studies revolve around understanding the qualitative composition and to quantify average structural parameters such as aromatic and aliphatic content, average chain length for aliphatic moieties, and average number of substituents on the aromatic ring.…”
Section: Introductionmentioning
confidence: 99%